The manifestations of words that are exposed to the phenomenon of economics in modern languages (Eurasian Journal of Philology Science and Education, 2019)
The article considers the peculiarities of the law of word savings in history of the Kazakh language,which is one of the parts of academic disciplines in higher educational institutions. In turn, it considers sounds, words and phrases that have been saved in any area of the Kazakh language. This process,which shows the progress of language history, as long as the law of word savings but also became themain subject for the scientists attraction which has considerably expanded the scope of the research.In the article, the process of word savings phenomena has been studied in phonetics, lexicology andsyntax. The language has proven to be a constantly changeable and saving phenomenon that does notlose its dynamic state. The article discusses this phenomenon not only in the general language, but alsoin the opinion of correspondent between scientists and Kazakh linguistics. It was found out that severalfactors have influenced the word saving phenomena in the Kazakh language as become the saving law.Examples of linguistic researches are the fact that in the history of linguistics, both in the modern Kazakhlanguage, the words that are exposed to the word saving phenomenon are proved.